“I Recall this Picture”: Understanding Picture Password Selections based on Users’ Sociocultural Experiences - Constantinides, Argyris; Fidas, Christos; Belk, Marios; Pitsillides, Andreas (2019 IEEE WIC ACM International Conference on Web Intelligence (WI), 2019)
Graphical passwords leverage the picture superiority effect to enhance memorability, and reflect today's haptic user interaction realms. Image content related to users’ past sociocultural experiences assists users with the creation of more secure and memorable passwords. Aiming to shed light on the effects of sociocultural-related image content towards graphical password selections, we conducted a between-subjects eye-tracking study (N=37) in which users selected one image among a set of images from their assigned image group (sociocultural-related vs. generic) that would be used for creating their graphical password. Results revealed differences in users’ interaction and visual behavior during image selection. Initial users’ feedback regarding the likeability and users’ engagement with the sociocultural-related image content is also presented.